Cara pandang hierarkis dan logika dominasi sebagai akar penyebab ketidakadilan gender dan kerusakan alam: Sebuah kritik teologi ekofeminis Kristen - Lakonawa, Petrus (KURIOS, 2024)
In a world that is still constrained by oppression, discrimination, and violence against others, this article attempts to critically examine the hierarchical worldview and the logic of domination using a Christian ecofeminist theological perspective. This article aims to provide critical notes on several theological views that inherit or contribute to perpetuating hierarchical worldview, the logic of domination, and asymmetrical relationships, especially those that have become the basis for the oppression of women and nature. This study uses text analysis methods within the framework of a qualitative literature study to analyze and outline the core ideas of the logic of domination and the main theses of Christian ecofeminist theology to overcome the common exclusive and discriminatory theological problems. This research concludes that a hierarchical worldview and the logic of domination have become the root causes of various asymmetric exploitative relationships that have given rise to gender inequality, environmental destruction, and various other structural injustices in the world. This article encourages the emergence of collective awareness to fight for the social and ecological transformation of exploitative life structures.   Abstrak Dalam dunia yang masih terkekang oleh penindasan, diskriminasi, dan kekerasan terhadap yang lain, artikel ini mengkaji secara kritis pandangan dunia hierarkis dan logika dominasi dengan menggunakan perspektif teologis ekofeminis Kristen. Artikel ini bertujuan untuk memberikan catatan kritis atas beberapa pandangan teologis yang mewarisi ataupun ikut melanggengkan cara pandang yang hierarkis, logika dominasi, dan relasi yang asimetris dalam kehidupan bersama, teristimewa yang telah menjadi dasar penindasan terhadap perempuan dan alam. Metode yang digunakan adalah analisis teks dalam bingkai studi kualitatif literatur, menguraikan ide-ide inti logika dominasi yang melahirkan pandangan teologi yang eksklusif dan diskriminatif. Penelitian ini menyimpulkan bahwa pandangan dunia hierarkis dan logika dominasi telah menjadi akar penyebab utama dari berbagai hubungan eksploitatif asimetris yang telah melahirkan ketidaksetaraan gender, perusakan lingkungan hidup, dan berbagai ketidakadilan struktural lainnya di dunia. Riset ini mendorong lahirnya kesadaran kolektif untuk memperjuangan transformasi sosial dan ekologis dari struktur-struktur kehidupan eksploitatif yang ada.